The exploratory study on performance of Village-Owned Enterprises (BUMDes) in Small Regency Bengkulu - Dri Asmawanti; Vika Fitranita; Ratu Eva Febriani (Jurnal Akuntansi dan Auditing Indonesia, 2022)
This study aims to examine factors that affect the performance of Village Owned Enterprises (BUMDes) and find out what problems BUMDes have in the Central Bengkulu Regency. This research used stewardship theory and Social Enterprise Theory. Researchers applied descriptive qualitative approach. The research informant was a village device/BUMDes manager. The results of this study showed that most BUMDes have business units and income of at least one million per month. The factors affecting their performance were business type, revenue, and management/ management of organizations. The problem faced by all BUMDes was BUMDes Human Resources (HR), which was not yet capable and competent, as well as knowledge and skills in conducting good financial management and reporting. The development of BUMDes' business unit, BUMDes management, and its ability to manage and account for its performance was the key to the success of BUMDes. Local governments should pay more attention and foster and increase supervision of the performance of BUMDes more intensely. The study used BUMDes performance categorization assessments attributed to the Building Village Index, specifically the Economic Resilience Index.